Validation of competence models for developing education standards: Methodological choices and their consequences - Ramseier, Erich (Mesure et évaluation en éducation, 2008)
Following PISA 2000, Switzerland launched a project called HarmoS (Harmonization of obligatory School) to develop binding education standards for compulsory education in the three language regions of the country. These standards for four subject areas are based on models of competence. Part of the development is an empirical study to validate these competence models. The present article describes the design, methods, and some results of this validation study. It also discusses the study’s usefulness for defining the standards and the consequences of some methodological choices, particularly the heuristic application of the Rasch model.